An In Situ Transmission Electron Microscopy Study of Localized Corrosion on Aluminum. Issue 25 (11th May 2016) - Pinkowitz, Ainsley; Chee, See Wee; Engler, Brent J.; Duquette, David J.; Hull, Robert
ABSTRACT: While the growth of pits in passive metals exposed to chloride solutions is well understood, the processes associated with the initiation and propagation of stable pits, versus pits that form and apparently re-passivate, are still a matter of conjecture. A major challenge in studying pit initiation using electron microscopy has been alteration of the structure and chemistry of the hydrated corrosion films upon transfer to the vacuum environment of the microscope. A recently developed technique uses a microfluidic liquid cell to maintain the aqueous environment in contact with the sample. This work uses such cells to directly observe pits initiating, and growing before reaching stability, in aluminum thin films under potentiostatic polarization in situ in the electron microscope. Polarization curves developed in the cell show good agreement with those observed under conventional electrochemical experimental conditions. We observed current transients representative of metastable pitting and were able to relate crystalline features found in situ with topographic features using atomic force microscopy (AFM). An accumulation of aluminum surrounding an initiated pit, combined with depth profiling using Auger electron spectroscopy suggests that aluminum metal is deposited during the pit initiation process, and may serve to reduce lateral dissolution of the aluminum film. Work is currently underway to determine if this observation is unique to the geometry of the microfluidics cell or if is a general result that occurs at the very beginning of pit initiation.